Hubungan Karakteristik Permukiman Kumuh terhadap Kejadian Keluarga Berisiko Stunting di Kelurahan Mantuil Kecamatan Banjarmasin Selatan Kota Banjarmasin - Fadillah, Alifia Salma; Nasruddin, Nasruddin (IAI Nasional Laa Roiba Bogor, 2025)
Slums in urban areas are often associated with various social and health problems, one of which is the increased risk of stunting in families. Dense environmental conditions, poor sanitation, and limited access to clean water are dominant factors that affect public health. This study aims to: (1) identify the characteristics of slums, (2) identify the characteristics of families at risk of stunting, and (3) analyze the relationship between slum characteristics and the incidence of families at risk of stunting in Mantuil Village, South Banjarmasin District, Banjarmasin City. The research method uses a quantitative approach with descriptive analysis and Chi-Square (χ²) statistical tests. Data were obtained through field observations and questionnaires from 100 respondents representing slum areas. Spatial analysis was conducted with the help of Geographic Information Systems (GIS) to map the distribution of slum areas and the location of families at risk of stunting. The results show that most areas of Mantuil Village have inadequate physical environmental conditions, with high building density and limited access to clean water and sanitation. Statistical test results showed a significant relationship between family income (p=0.000), residential density (p=0.003), feeding practices (p=0.000), access to sanitation (p=0.016), access to clean water (p=0.027), and access to health services (p=0.001) and the incidence of families at risk of stunting. Meanwhile, maternal education did not show a significant relationship (p=0.072). This study concluded that slum characteristics significantly influence the increased risk of stunting in families. Therefore, improving the quality of residential environments, providing clean water, and improving sanitation systems need to be prioritized in stunting prevention efforts in urban areas.